PENATALAKSANAAN FISIOTERAPI PADA DEQUERVAIN SYNDROME MENGGUNAKAN ULTRASOUND, TENS DAN TERAPI LATIHAN DI RSUD KRATON KAB. PEKALONGAN - Hendra Yusuf; Irine Dwitasari Wulandari (LPPM Universitas Pekalongan, 2013)
De Quervain syndrome is a painful problem which obtained by an inflammation at tendons on wrist area exactly at the thumb area (Ilyass, 2008).The problems that will occure on De Quervain syndrome is pain, edema, spasm, limitation of ROM, decreased muscle strength and decreased of functional ability. The examination that conducted are measurement of pain with VAS measurement of (Visual Analogue Scale), edema with anthropometry, Spasms by palpation, ROM with gonemeter, muscle strength by MMT (Manual Muscle Testing) and functional ability with ADL index (Activity Daily Living). In this case to solve the problems are with Ultrasound (US), Transcutaneous Electrical Nerve Stimulation (TENS) and exercise therapy, after conducted physiotherapy management as much as six times obtained results among decreased of pain, decreased of edema, decreased of spasm, increased ROM, increased muscle strength and increased of functional ability .Keywords :De Quervain syndrome, Ultrasound, TENS, Aktive movement